Identification of Flavonoid Content Extracted from Mangosteen Peel (Garcinia mangostana) Sourced from Mataram, West Nusa Tenggara - Muahiddah, Nuri; Rahmadani, Thoy Batun Citra (Journal of Fish Health, 2024)
Mangosteen peel (Garcinia mangostana) is known for its high concentration of bioactive compounds, particularly flavonoids, which possess various health benefits such as antioxidant, anti-inflammatory, and antimicrobial properties. This study aims to identify and quantify the flavonoid content extracted from mangosteen peels sourced from Mataram, West Nusa Tenggara. Using ethanol as a solvent, the extraction process was carried out through maceration, followed by qualitative and quantitative analysis using Fourier Transform Infrared Spectroscopy (FT-IR). The FTIR analysis confirmed the presence of key functional groups associated with flavonoids, including hydroxyl (-OH), ether (C-O), and aromatic C=C groups. Quantitative analysis revealed a significant flavonoid content. Additionally, the extract showed potential antibacterial properties against Aeromonas hydrophila, suggesting its application as a natural antimicrobial agent.